Key information systems management Issues: A comparative study in South Africa - M. L. Hart; S. Berkowitz; J. Ryan; K. Waspe (South African Journal of Business Management, 2004)
The identification of key Information Systems (IS) management Issues is important for all players in the industry. Most academic research has followed the form of the Society for Information Management (SIM) studies, originating in the early 1980's in the United States of America (USA), and since replicated in many countries, yet no comprehensive recent study had been carried out in South Africa. This study was performed within weeks of September 11, 2001 on a sample of 121 members of the Cape IT Initiative (CITI), and of the Computer Society of South Africa (CSSA), from a range of industries and geographical regions. Highest rated Issues were business intelligence, a responsive IT infrastructure and disaster recovery, while Business Relationship and Technical Infrastructure Issues were prominent overall. Demographic factors did not significantly influence overall results. Rankings were correlated with an earlier South African study and with 1997 Australian research, but not with a 1995 USA study. The economic developmental status of a country was found to be linked to the key Issues that country faces.
Keywords: 650